Trinitarian Theology : Theological Models and Doctrinal Application. - Whitfield, Keith (B & H Publishing Group, 2019)
In Trinitarian Theology, contributors Bruce Ware, Malcon B. Yarnell III, Matthew Y. Emerson, and Luke Stamps discuss theological methods for forming the doctrine of the Trinity, and the the implications in applying that doctrine to complementarianism.